Construction of The Qur'anic Education Thought of Tgh. Musthofa Umar Abdul Aziz Lombok - Nazopah, Nada; Fadli, Adi; Emawati (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Islamic education is deeply rooted in Qur'anic education, which serves as its philosophical foundation, motivating Muslims to engage in the study and memorization of the Qur'an. This paper explores the educational philosophy of TGH. Musthofa Umar Abdul Aziz, a renowned cleric in Lombok and beyond, known for founding the Al-Aziziyah Islamic Boarding School, a center for Qur'anic memorization. Through a qualitative library research approach, the study analyzes TGH. Musthofa's writings and related literature, drawing on perspectives from psychology, sociology, and education. The findings reveal that his Qur'anic education system emphasizes cultivating a generation with a clear understanding of the Qur'an, detailed hadiths, and the practiced sunnah. His educational philosophy starts with memorization, progressing to scholarly development. The educator's role is to guide students who learn to read, memorize, understand, and apply the Qur'an, using methods like Iqro for reading and Talaqqi for memorization. The curriculum and evaluation processes are designed to achieve these objectives, ensuring that Qur'anic education fosters both intellectual and spiritual growth.